Evolução metabólica e ponderal de pacientes adultos atendidos em ambulatório de nutrição, utilizando uma abordagem comportamental - ARAÚJO, Letícia Mendes de (2023)
The progressive worldwide growth of obesity and non-communicable chronic diseases points to the low effectiveness of the strategies used in their treatment. The objective of this study was to evaluate the impact of the behavioral nutrition approach on metabolic parameters and body weight of adult patients treated at the João de Barros Barreto University Hospital. The parameters evaluated before and after the nutritional intervention were body weight and serum concentrations of glucose, triglycerides, total cholesterol, HDL cholesterol, LDL-cholesterol and non-HDL-cholesterol. It was a practical, quantitative, observational, exploratory study with the collection of secondary data from electronic medical records, which had a non-probabilistic sample of 18 individuals. Of these, 67% were women. The distribution of variables was tested using the Kolmogorov-Smirnov test and then the t or Wilcoxon tests were applied in cases of normal or non-normal distribution, respectively, to compare the median of the differences before and after the nutritional intervention. Type 2 diabetes mellitus was the most prevalent underlying disease. With the exception of HDL-c, all metabolic parameters and weight improved significantly after the behavioral nutritional intervention.